P210 Use of dexmedetomidine with non-invasive ventilation (NIV) in a cardiothoracic intensive care unit (CT ICU). (December 2018) - Masding, A; Keating, O; Pereira, C; Kaul, S
Abstract : Background: The use of sedatives in NIV is controversial. Evidence –base for dexmedetomidine in patients requiring NIV is conflicting. We report the use of dexmedetomidine in patients requiring NIV in a UK Tertiary CT ICU. Aim: We report physiological data, patient outcomes; re-intubation and tracheostomy rates, length of stay (LoS) and survival, and the safety of dexmedetomidine in patients post-extubation requiring NIV in acute respiratory failure. Methods: Design: Retrospective single-centre observational study. Setting: UK Tertiary CT ICU. Results: 18 patients (66 (24–86) years; 78% male) were included. Indications for ICU admission included post-cardiac surgery (33.3%; n=6), cardiology (33.3%; n=6) and post-transplant (16.7%; n=3). Dexmedetomidine initiated for delirium (median RASS score of 2). Median duration of dexmedetomidine 21 hour (3–56 hour). Indications for NIV included type 1 respiratory failure (T1RF) (55.6%; n=10), of which pneumonia was the most common cause (60% T1RF cases), and type 2 respiratory failure (38.9%; n=7); most common causes were pneumonia (28.6%) and cardiogenic pulmonary oedema (28.6%). Lowest pH was 7.16. Median time to pH normalisation on NIV 16.1 hour (4.9–19.1 hour). Average duration of NIV was 28.9 hour. NIV with dexmedetomidine was successful in most patients (71%; n=11). 39% (n=7) required re-intubation ±tracheostomy, of which 57.1% (n=4) were secondary to progressive T1RF despite NIV. ICU length of stay (LoS) was significantly greater in patients with NIV failure requiring re-intubation and tracheostomy (16.7%; n=3), but was not greatly if patients did not require tracheostomy (table 1). Overall ICU mortality was 22.2% (n=4), of which 50% had required re-intubation post-NIV and one patient had mixed acidosis. Causes of mortality were un-related to sedation/NIV and included undrainable pericardial effusion, cardiogenic arrhythmia, and sepsis related to multi-organ failure. Conclusions: To our knowledge this is the first report of the use of Dexdor in patients requiring NIV post-extubation in a UK Cardio Thoracic ICU. Patients with acute respiratory failure and delirium can be safely and feasibly managed with NIV, with avoidance of intubation in over two thirds of patients and no observed increase in mortality. The importance of monitoring these patients whom are at risk of re-intubation in an appropriate setting cannot be over-emphasized.